Avaliação das atividades cicatrizante e antiinflamatória de Casearia sylvestris Swartz em animais e identificação dos marcadores químicos - Pierri, Elaise Gonçalves [UNESP] (2013)
Casearia sylvestris Sw (Salicaceae) is a tree or shrub known as guaçatonga used in folk medicine for its antiseptic, antiophidian, antiulcerogenic, anti-inflammatory and wound healing properties. From the leaves it was developed pretreatment and quality control, in order to characterize the plant as pharmaceutical raw material. The ethanol extract was produced from 2.0 kg of the plant drug, and the extraction yield was 11.8% (w/w).It was performed a solid phase extraction (EFS) with 20.0 g of the ethanol extract of dried leaves of C. sylvestris. The purification was carried out in three steps, including a solid phase extraction by means of silica and activated carbon, normal-phase column chromatography and aqueous reversed-phase high efficiency chromatography. The diterpenes caseargrewiin F, casearins B and X. were used as standards. The clerodane type diterpenes were identified and quantified via HPLC-DAD in the extract EEtCs and EFSCs2 fraction whose values were 27.4% and 50.6%, respectively. From EFSCs2 fraction it was isolated a substance identified via spectrometric analysis as casearin J, existing in the literature. From the HPLC-UV analysis the casearin J and caseargrewiin F contents were gotten in the leaves ethanol extract, which values were 2.35 and 1.1% respectively. In order to evaluate the anti-inflammatory activity, rat's paw edema was performed where the results were promising regarding to indomethacin and, either extract (EEtCs), fractions (EFSCs 1 and 2) and purified substances (Cas B and CasgwF) showed no gastric wound in the animals stomach when macroscopically examined, in opposite to indomethacin that showed wound level 5 (maximum) on the ulceration index. In the chronic anti-inflammatory activity (arthritis) the reestablishment of the joints proportion for the group treated with dexamethasone (1 mg / kg) was 80 % and for the group treated with the ...